Marketing strategy of VER ARI s.r.o. for the construction market - Chapaeva, Veronika (2024)
The thesis focuses on developing and justifying marketing strategies for VER ARI s.r.o. in the Czech residential construction market. It provides an introduction to the company's background and operations, emphasizing the importance of market segmentation and targeting for business growth. The thesis is divided into three main sections: the first section outlines theoretical concepts related to market segmentation and targeting strategies, the second section presents an analysis of primary and secondary data, including qualitative interviews with B2B and B2C segments, and the third section formulates practical marketing recommendations for VER ARI s.r.o. The research explores key factors such as customer needs, personalized service, construction quality, and eco-friendly practices. The findings lead to actionable strategies aimed at enhancing VER ARI s.r.o.'s market position and ensuring sustainable growth in the competitive Czech residential construction industry.